Ittijahat al-Tullab fi Kulliyyat Dirasat al-Lughat al-Ra’isah Nahw Ta’allum al-Balaghah al-’Arabiyyah ’Abr Barnamaj al-Wasa’it al-Muta’addidah - Mohd Shahrizal, Nasir; Nurkhamimi, Zainuddin; Muhammad Sabri, Sahrir (2016)
This study discusses in details the practical steps concerning the development of multimedia program for teaching Arabic Rhetoric. 160 third year students from Fakulti Pengajian Bahasa Utama, Universiti Sains Islam Malaysia had participated in the study which was carried out during the semester two of 2014/2015 academic year. After the end of the development process, a pilot study was used to confirm if the multimedia program for teaching Arabic Rhetoric is ready for full-scale implementation. An informal interview (think-aloud method) has been conducted with the students during the process of learning Arabic Rhetoric. The outcome of the interview proposed the use multimedia program as a tool is for enhancing their desires in learning Arabic Rhetoric as they are found to be highly motivated and engaged in the learning process.